Research progress of exosomes in pathogenesis, diagnosis, and treatment of ocular diseases - Feng, Xinting; Peng, Zhen; Yuan, Lingyi; Jin, Ming; Hu, Haijian; Peng, Xin; Wang, Yaohua; Zhang, Chun; Luo, Zhiwen; Liao, Hongfei (Frontiers in Bioengineering and Biotechnology, 2023)
Exosomes are natural extracellular vesicles with a diameter of 30-150nm, which exist in biological fluids and contain biomolecules related to the parent cell, such as proteins, nucleic acids, lipids, etc. It has a wide range of biological functions, and participates in the regulation of important physiological and pathological activities of the body. It can be used as a biomarker for early diagnosis of ocular diseases, a potential therapeutic target, a targeted drug carrier, and has a high potential for clinical application. In this paper, we summarized the genesis mechanism, biological functions, research and application progress of exosomes, focused on the engineering strategy of exosomes, and summarized the advantages and disadvantages of common engineering exosome preparation methods. Systematically combed the role of exosomes in corneal diseases, glaucoma, and retinal diseases, to provide a reference for further understanding of the role of exosomes in the pathogenesis, diagnosis, and treatment of ocular diseases. Finally, we further summarized the opportunities and challenges of exosomes for precision medicine. The extension of exosome research to the field of ophthalmology will help advance current diagnostic and therapeutic methods. Tiny exosomes have huge potential.